The Role of GDF-15 in Heart Failure Patients With Chronic Kidney Disease - Benes, Jan; Kotrc, Martin; Wohlfahrt, Peter; Conrad, Michael J; Franekova, Janka; Jabor, Antonin; Lupinek, Petr; Kautzner, Josef; Melenovsky, Vojtech; Jarolim, Petr (Canadian journal of cardiology, 2019)
BACKGROUND: Growth differentiation factor-15 (GDF-15) is a stress-inducible cytokine and member of the transforming growth factor-β cytokine superfamily that refines prognostic assessment in subgroups of patients with heart failure (HF). We evaluated its role in HF patients with chronic kidney disease (CKD, estimated glomerular filtration rate <60 mL/min/1.73 m2). METHODS: A total of 358 patients with stable systolic HF were followed for a median of 1121 (interquartile range, 379-2600) days. Comprehensive evaluation including B-type natriuretic peptide (BNP) and GDF-15 testing was performed at study entry; the analysis was stratified according to kidney function. RESULTS: Patients with CKD (33.8%) were older, had more often diabetes, and were less often treated with angiotensin converting enzyme inhibitors (ACEi)/angiotensin receptor blockers (ARB). GDF-15 was associated with estimated glomerular filtration rate, whereas BNP was associated with left ventricular-end diastolic diameter and ejection fraction (P < 0.01). During follow-up, 244 patients (68.2%) experienced an adverse outcome (death, urgent transplantation, implantation of mechanical circulatory support). In patients with HF and CKD, the Cox proportional hazard model identified BNP, GDF-15, sex, systolic blood pressure, sodium, total cholesterol, and ACEi/ARB treatment as significant variables associated with an adverse outcome (P < 0.05). In multivariable analysis, BNP was replaced by GDF-15. Net reclassification improvement confirmed prognostic superiority of the model encompassing GDF-15 (GDF-15, sodium, total cholesterol, ACEi/ARB treatment) compared with the model without GDF-15 (BNP, sex, sodium, ACEi/ARB treatment), net reclassification improvement 0.62, P = 0.005. In contrast, in patients with HF and normal kidney function, BNP remained superior to GDF-15 in a multivariable model. CONCLUSIONS: In patients with systolic HF and CKD, GDF-15 is more strongly associated with adverse outcomes than the conventionally used BNP.
Keywords: Heart Transplantation; cholesterol; Female; Sodium; systola; biologické markery; antagonisté receptorů pro angiotenzin; Biomarkers; ženské pohlaví; růstový diferenciační faktor 15; Glomerular Filtration Rate; Heart Failure, Systolic; Renal Insufficiency, Chronic; Heart-Assist Devices; inhibitory ACE; lidé; Natriuretic Peptide, Brain; systolické srdeční selhání; následné studie; Angiotensin-Converting Enzyme Inhibitors; chronická renální insuficience; krevní tlak; Cholesterol; Sex Factors; natriuretický peptid typu B; proporcionální rizikové modely; Follow-Up Studies; Male; sodík; podpůrné srdeční systémy; sexuální faktory; Growth Differentiation Factor 15; Proportional Hazards Models; Systole; transplantace srdce; lidé středního věku; mužské pohlaví; Angiotensin Receptor Antagonists; Blood Pressure; Middle Aged; hodnoty glomerulární filtrace; Humans